THE INFLUENCE OF PRICE, TRUST AND SERVICE QUALITY ON CUSTOMER LOYALTY IN CAR RENTAL SERVICE COMPANIES IN GRESIK DISTRICT - Erwan Aristyanto (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This research aims to analyze and determine the influence of price, trust and service quality on customer loyalty in car rental services in Gresik Regency. The data collection method used is questionnaire data with a quantitative approach. The research instrument uses a Likert scale and the technique used uses a Non-Probability Sampling technique with an Accidental Sampling approach. The population is all customers at car rental services in Gresik Regency by taking a sample of 110 customers. The data analysis method used is multiple linear regression analysis using the SPSS statistical test tool. The research results show that the Price Variable partially has a significant effect on Customer Loyalty in Car Rental Services in Gresik Regency. The trust variable partially has a significant effect on customer loyalty to car rental services in Gresik Regency. Partial service quality does not have a significant effect on customer loyalty to car rental services in Gresik Regency. The variables price, trust and service quality simultaneously have a significant effect on customer loyalty to car rental services in Gresik Regency.